Magyarországi diákok hollandiai teológiai tanulmányai levéltári források tükrében - Bozzay, Réka (Gerundium, 2017)
Theological studies of Hungarian students in the Netherlands based on archival sources. Hungarian peregrination found their new routes after having banned Calvinists students from Wittenberg and after the fall of Heidelberg. Hungarian students visited Dutch universities from the end of the 16 th century till 1795 when French troops occupied the Netherlands. Most of the Hungarian protestants were Calvinists and the main goal of the peregrination academica was the education of Hungarian Calvinist clergymen. This papers aims at presenting the most important theological movements based on archival sources which originated from the Netherlands or reached the Hungarians Calvinist church through the Dutch universities: arminianism, puritanism and coccejanism. Hungarian representatives of these theological movements, their theological debates in the Netherlands and in their home church and furthermore their influence on the Hungarian/Transylvanian Calvinist church will be mentioned. In the last part I will examine the theological exams, testimonials and dissertations of becoming Calvinist theologists.